FAIR data in metabolomics - Steinbeck, Christoph (Henry Stewart Talks, 2017)
Introduction to metabolomics, phenome and exposome, Metabolomics on the rise, Phenome centres, Data sharing and FAIR data, MetaboLights database, ISA toolkit, COSMOS, MetabolomeXchange